Analisis Efektivitas Pengelolahan Dana Bantuan Operasional Sekolah (BOS) Di SMA Negeri 1 Telaga Kabupaten Gorontalo - Antika, Ririn; Abdullah, Julie; Hasan, Wahyudin (CV. ITTC INDONESIA, 2023)
The purpose of this study is to analyze the effectiveness of the manement of School Operational Assistance (BOS) funds. The methods used in this study are quantitative methods, data collection techniques with observation, interviews and documentation. The results of the study showed that the BOS funds at SMA Negeri 1 Telaga were evvetife because the school budget activity plan (RKAS) and budget realization are in accordance with what was previously budgeted so that it is said to be effective